PENGARUH PEMBERIAN DOSIS PUPUK KANDANG KAMBING DAN PUPUK MKP TERHADAP PERTUMBUHAN DAN HASIL KEDELAI EDAMAME (Glycine max (L) Merrill) - Stefani Vivilia Y. Markus; Ida Bagus Komang Mahardika; Luh Kartini (Fakultas Pertanian, Universitas Warmadewa, 2025)
This study aims to analyze the effect of giving doses of goat manure and MKP fertilizer on the growth and yield of edamame soybean plants (Glycine max (L) Merrill) and their interactions. This research was carried out in the Greenhouse of the Faculty of Agriculture, Warmadewa University, Jalan Terompong No. 24, Sumerta Kelod, East Denpasar District, Denpasar City from January to March 2023. The research method used was a Randomized Block Design (RAK) with 2 factors arranged factorially. The first factor is the provision of goat manure (K) which consists of 4 levels, namely: K0 = Control (0 ton. ha-1), K1 = 10 tons.ha-1, K2 = 20 tons.ha-1, K3 = 30 tons.ha-1. The second factor uses MKP (M) fertilizer which consists of 4 levels, namely: M0 = 0 grams.liter-1, M1 = 4.5 grams.liter-1, M2 = 9 grams.liter-1, M3 = 13.5 grams.liter-1. And repeated 3 times so that 48 polybags were needed. The results of statistical analysis showed that the treatment dose of goat manure had a significant effect (P<0.05) on the number of pods and fresh weight of fruit stalks per plant. The highest number of pods per plant was obtained in the treatment without 0 ton.ha-1 (K0) goat manure, namely 64.08 pieces, an increase of 31.90% compared to the 20 ton.ha-1 (K2) goat manure treatment with the lowest number of pods was 48.58 pieces. The highest fresh weight per plant was found in the treatment without 0 ton.ha-1 (K0) goat manure, namely 165.60 grams, an increase of 31.07% when compared to the lowest result in the 20 ton.ha-1 goat manure treatment. (K2) which weighs 129.39 grams. The treatment dose of MKP fertilizer had a significant effect (P<0.05) on the oven dry weight of seeds per plant. The highest oven dry weight of seeds per plant was obtained in the treatment without a dose of 0 gram.liter-1 MKP fertilizer, namely 12.40 grams, an increase of 68.24% when compared to the lowest result in the 9 gram.liter-1 (M2) MKP fertilizer treatment, namely weighing 7.37 grams.